(untitled) (Web of Teachers: Inderscience Research, 2024)
Public safety is one of the main pillars of every society. Security is necessary for citizens to live a peaceful life. Cooperation between state bodies, local communities, citizens and other organizations is necessary to ensure public safety. This article discusses the importance of public safety cooperation, its basic principles, benefits and practical examples.